THE EFFECT OF PROMOTION AND COMMUNICATION ON PRODUCT SELLING POWER WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE ON CV. TABEK RAYA P&D SOLOK CITY - Rahman, Naufal; Salim, Emil; Putri, Della Asmaria (Jurnal Bisnis Digital, 2024)
This research aims to determine and try to analyze the influence of promotion and communication on product selling power with consumer satisfaction as an intervening variable in CV. Tabek Raya P&D Solok City. This research is a Structural Equation Modeling (SEM) model with the Smart PLS 3.0 analysis tool. The population and sample of this research are CV consumers. Tabek Raya P&D Solok City. The research results found that there is an influence between Promotion and Consumer Satisfaction. There is an influence between Communication and Consumer Satisfaction. There is an influence between Promotion and Product Selling Power. There is no influence between Communication on Product Selling Power. There is an influence between Consumer Satisfaction on Product Selling Power. Consumer Satisfaction mediates Promotion on Product Selling Power. Consumer Satisfaction mediates Communication on Product Selling Power